2022
DOI: 10.26508/lsa.202201572
|View full text |Cite
|
Sign up to set email alerts
|

The MLL3/4 complexes and MiDAC co-regulate H4K20ac to control a specific gene expression program

Abstract: The mitotic deacetylase complex MiDAC has recently been shown to play a vital physiological role in embryonic development and neurite outgrowth. However, how MiDAC functionally intersects with other chromatin-modifying regulators is poorly understood. Here, we describe a physical interaction between the histone H3K27 demethylase UTX, a complex-specific subunit of the enhancer-associated MLL3/4 complexes, and MiDAC. We demonstrate that UTX bridges the association of the MLL3/4 complexes and MiDAC by interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Furthermore, MiDAC has been implicated in gene expression during neurite outgrowth in mice [70] and the negative regulation of the H4K20ac histone modification [71]. Our findings that 1) DNTTIP1 directly recognizes TASHET DNA in vitro and in cellulo (Figs A role for DNTTIP1 in transcription was shown by placing DNTTIP1 consensus sites 5' of a minimal promoter where they produced increased reporter gene expression in response to DNTTIP1 overexpression [50].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, MiDAC has been implicated in gene expression during neurite outgrowth in mice [70] and the negative regulation of the H4K20ac histone modification [71]. Our findings that 1) DNTTIP1 directly recognizes TASHET DNA in vitro and in cellulo (Figs A role for DNTTIP1 in transcription was shown by placing DNTTIP1 consensus sites 5' of a minimal promoter where they produced increased reporter gene expression in response to DNTTIP1 overexpression [50].…”
Section: Discussionmentioning
confidence: 56%
“…Recent work has shown that MiDAC is essential for embryonic development in mice and forms a unique multivalent structure [69]. Furthermore, MiDAC has been implicated in gene expression during neurite outgrowth in mice [70] and the negative regulation of the H4K20ac histone modification [71]. Our findings that 1) DNTTIP1 directly recognizes TASHET DNA in vitro and in cellulo (Figs 3 & 4), 2) DNTTIP1, MIDEAS, and NAT10 are required for full HIV transcription (Figs 5 & 6), and 3) NAT10 associates with MIDEAS (Fig 2), together with published data showing that NAT10 interacts with HIV Tat [38, 39], support a model in which MiDAC is recruited to TASHET via the binding of its DNTTIP1 subunit (Fig 8).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that MiDAC is essential for embryonic development in mice and forms a unique multivalent structure [ 70 ]. Furthermore, MiDAC has been implicated in gene expression during neurite outgrowth in mice [ 71 ] and the negative regulation of the H4K20ac histone modification [ 72 ]. Our findings that 1) DNTTIP1 directly recognizes TASHET DNA in vitro and in cellulo (Figs 3 and 4 ), 2) DNTTIP1, MIDEAS, and NAT10 are required for full HIV transcription (Figs 5 and 6 ), and 3) NAT10 associates with MIDEAS ( Fig 2 ), together with published data showing that NAT10 interacts with HIV Tat [ 38 , 39 ], support a model in which MiDAC is recruited to TASHET via the binding of its DNTTIP1 subunit ( Fig 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…PR-DUB binding is compromised by cancer mutations in MLL3 and could be partially balanced by UTX in an experimental setting [ 11 ]. Recent studies have also demonstrated the interaction of UTX with the mitotic deacetylase complex (MiDAC) [ 12 , 13 ]. Interestingly, UTX escapes X inactivation in females, which is compensated for in males by the chromosome Y encoding the UTY ortholog (also referred to as KDM6C) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%